Impact of an Educational program on Teachers’ Knowledge Toward Chickenpox Prevention at Primary Schools in Al-Najaf Governorate - Raid Saad Atshan1 , Asmahan Qasim Mohammed2 , Ali Hussien Abbas3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Chickenpox disease is one of a highly infectious disease caused by the virus called varicella zoster.Chickenpox is spread through coughing and sneezing, and through direct contact with fluids in rashes. Mostpeople who are vulnerable to chickenpox are children, especially those under 12 years old. Objectives:The study aim determine the effective of education programs on teachers’ knowledge toward children withof chickenpox disease at Primary schools in Al-Najaf governorate and the relationship between teachers’knowledge with their demographic variables. Methodology: A quasi experimental studies was carriedout at Primary schools in Al-Najaf governorate from January 2019, to the end of April 2020, the samplewas collected in a purposive random sample comprised with 12 schools, identified the number of teachersselected from each school was 45, the data were collected using a questionnaire consisting of two main parts,the first part related to the social and demographic characteristics of teachers, and the second part concernedteachers’ knowledge about the prevention of chickenpox and then an educational program was establishedto increase the awareness and knowledge of teachers towards the prevention of chickenpox. Results: Theresults showed that most of the samples (37.8%) were aged between (41- 50) years. For the number ofyears of service, the greatest percentage (35.6%) of the sample ranged from 1 to 10 years, the study alsoshowed that 100% of the questions were answered by the teachers after the impact of the educationalprogram. Conclusion: The study concludes that the effectiveness of an education program toward teacher’sknowledge, which is concerned with chickenpox, is positive at a high rate.